Propuesta de un plan de negocios para la producción y comercialización de panetones en el Distrito de TRUJILLO” - Olazo Balarezo, Lucero (2017)
In this thesis the development, implementation and results of the market study that seeks to measure the commercial feasibility of panettone in the district of Trujillo explained. A description of the business idea was made, formulation of a marketing plan, analysis of an operating plan; description of the administrative structure; Description of financial management and economic evaluation of the project. item information was collected in the local environment. The tool applied was the survey, which showed us a detailed view of our target audience: the openness to new experiences, their habits and their preferred places to buy your product. Besides the existing demand for panettone in the district of Trujillo it was determined. Could identify points for product distribution and marketing possible price. In addition, an advertising and promotion plan that allows positioning our brand in the market developed trujillano. Finally it was concluded that there is a great demand for panettone in the city of Trujillo, since according to the financial evaluation has to: VAN E = S /. S /. 597,801.69 and the TIR E= 231.50% .For what is considered a profitable business despite competition, as a base product in the diet of trujillanos